Nosotros : a study of everyday meanings in Hispano New Mexico - Korte, Alvin O. (Latinos in the United States series., 2012)
Much knowledge and understanding can be generated from the experiences of everyday life. In this engaging study, Alvin O. Korte examines how this concept applies to Spanish-speaking peoples adapted to a particular locale, specifically the Hispanos and Hispanas of northern New Mexico. Drawing on social philosopher Alfred Schutz's theory of typification, Korte looks at how meaning and identity are crafted by quotidian activities. Incorporating phenomenological and ethnomethodological strategies, the author investigates several aspects of local Hispano culture, including the oral tradition, leave-taking, death and remembrances of the dead, spirituality, and the circle of life. Although avoiding a social-problems approach, the book devotes necessary attention to mortificacin (the death of the self), desmadre (chaos and disorder), and mancornando (cuckoldry). Nosotros is a vivid and insightful exploration with applications in numerous fields.